Effect of Applying the Make A Match Type Cooperative Learning Model on Thematic Learning Outcomes of Grade V Elementary School Students - Pangestu, Deviyanti; M, Muhisom; Habibi, Roy Kembar; Deyalita, Pricilia (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2022)
The problem in this study is the low thematic learning outcomes of fifth grade students at SD Negeri 1 Marga Agung which are not in accordance with the law which states optimizing the role of educators and improving the quality of educators. The aim of the study was to determine the effect of applying the make a match type cooperative learning model on thematic learning outcomes by mastering concepts and empirical experience in mastering innovative learning strategies for educators. The method used in this study was a quantitative research with an experimental type using the nonequivalent control group design technique using two classes as the sample to be studied, namely class VA and as the experimental class and class VB as the control class with a sample size of 33 students. The results of the study showed that there was a significant effect of applying the make a match cooperative model to the thematic learning outcomes of fifth grade students at SD Negeri 1 Marga Agung for the 2021/2022 academic year.